THE EFFECTS OF CORPORATE GOVERNANCE ON THE PROFITABILITY OF COMPANIES IN THE FIELD OF PUBLIC WATER SUPPLY SERVICES IN THE REPUBLIC OF MOLDOVA - TIMUȘ, Ana (Economy and Sociology, 2021)
In the Republic of Moldova, in the field of public water supply services, corporate governance, from a conceptual and regulatory point of view, began to develop only in the early 2010s. The selected topic is current because corporate governance is at the early stage in this field, but, at the same time, its evolution for 10 years needs to be analyzed. This process must be monitorized to identify the most important successes or deficiencies in order to develop a set of good practices. The purpose of the research is to identify the relationship between degree of development of corporate governance and the profitability of companies in the field as well as shaping the corporate governance model. Research methods used refer to the observation of corporate and economic processes, interview, investigation, comparing, analysis of corporate legislative and regulatory documents in the field, induction, explanation and interpretation of the main indicators of corporate management. The relevant research results are: identifying the fact that there is no clear dependence between the application of corporate management and increasing the profitability of water companies; at the same time, it has been identified that the participation of employees of water companies in the company boards contributes to better profitability. The corporate governance model was configured, with the identification of deficiencies in the process of regionalization of services. Corporate governance, in the analyzed field, must be subjected of the process of continuous improvement in particular by evaluating the activity of the company’s board.